Physical activity after kidney transplant - Polski, Paweł; Alzubedi, Adam; Kusz, Monika; Rudzki, Sławomir (Journal of Education, Health and Sport, 2018)
Chronic kidney disease is currently included in one of the civilization diseases. From year to year, the number of people suffering from this disease is systematically increasing. It is estimated that it affects about 30% of people over 60 years of age. Below this age, the number of patients is over 150 people with a million population. The increase in the number of cases is closely related to the change in the mode and pace of life in the modern world. Diabetes and hypertension are considered to be the main causes of kidney disease. Another point are glomerulonephritis. Chronic kidney disease is a progressive disease, and treatment is mainly based on slowing the pace of its progression or preventing complications. We distinguish three main methods of renal replacement therapy: peritoneal dialysis, hemodialysis and kidney transplantation. The first two methods prevent the occurrence of complications of kidney disease. However, they do not constitute a causal treatment. Renal replacement therapy is a significant burden for the patient. It involves many sacrifices and limitations in everyday functioning. Patients are forced to visit hemodialysis stations several times a week, which provides them with fairly average career and leisure opportunities. Currently considered the best method of combating chronic kidney disease is transplantation. Patients after kidney transplantation are able to return to life in a short period of time training. Also, the number of restrictions related to practicing sports is significantly reduced. The only obligation for patients after kidney transplantation is the regular intake of immunosuppressive drugs and controls in transplantation outpatient departments. This publication aims to present the possibilities and limitations for patients who want to actively rest and play sports